Analysis of Secondary Metabolite Compounds in Combination Extract of Red Castor Leaves (Jatropha gossypiifolia L) and Butterfly Pea Flowers (Clitoria ternatea L) - Putri, Bq Dinda Ayuni Rusma; Sabariah, Sabariah; Rini, Setio; Setiawan, Nyoman Cahyadi Tri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Red physic nut leaves (Jatropha gossypifolia L.) and butterfly pea flowers (Clitoria ternatea L.) are medicinal plants known to contain various secondary metabolites with potential applications in the pharmaceutical field. Secondary metabolites such play an important role as natural bioactive compounds. This study aimed to determine the presence of secondary metabolite compounds in the extracts of red physic nut leaves and butterfly pea flowers through phytochemical screening tests. This research was an experimental laboratory study. Samples of red physic nut leaves and butterfly pea flowers were dried, powdered, and extracted using the maceration method with 96% ethanol solvent for 3 × 24 hours with periodic stirring. The filtrate obtained from maceration was filtered and evaporated to obtain a thick extract. The extracts were then qualitatively analyzed using phytochemical screening methods to detect alkaloids (Mayer, Wagner, and Dragendorff reagents), flavonoids (Shinoda test), saponins (foam test), tannins (FeCl₃ test), as well as steroids and terpenoids (Liebermann–Burchard test). The phytochemical screening results showed that the extracts of red physic nut leaves and butterfly pea flowers were positive for several groups of secondary metabolites. Both extracts were identified to contain flavonoids, saponins, and tannins, while alkaloids, steroids, and terpenoids showed varying results in each extract. Based on these findings, it can be concluded that red physic nut leaves and butterfly pea flowers have the potential to serve as sources of natural bioactive compounds for further natural product–based research.